The Sultan Ahmet Mosque restoration works between 1988-1990 - Güralp, A (WIT PRESS, 1999)
The Sultan Ahmet Mosque was built under the instruction of Sultan 1. Ahmet. The Architect of the mosque was Sedefkar Mehmet Aga. He begun to build the Mosque in 1609, and finished it in 1614. Inside the mosque, blue Iznik mosaics were used. This is why it is called the Blue Mosque. Until today, many restoration works were done. Especially in 1888-1895, restoration works were very impotant. After this restoration, the most important restoration was in 1988 - 1990. In this paper the last restoration work will be explained. The restoration works may be grouped under seven headings: 1- Work on main dome, 2- Restoration of the stained - glass windows, 3- Restoration of the wooden shutters, 4- Repair of the floors, 5- Disassembling the scaffolding and cleaning, 6- Repair of outer stone wall, 7- The dome's lead plating and care of the cupola.
Keywords: Architecture; Construction & Building Technology; Engineering